2022
DOI: 10.15252/embr.202255432
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP R negatively regulates transcription by modulating the association of P‐TEFb with 7SK and BRD4

Abstract: The P‐TEFb complex promotes transcription elongation by releasing paused RNA polymerase II. P‐TEFb itself is known to be inactivated through binding to the non‐coding RNA 7SK but there is only limited information about mechanisms regulating their association. Here, we show that cells deficient in the RNA‐binding protein hnRNP R, a known 7SK interactor, exhibit increased transcription due to phosphorylation of RNA polymerase II. Intriguingly, loss of hnRNP R promotes the release of P‐TEFb from 7SK, accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition to its role in tumors, growing evidence has demonstrated that HNRNPR plays a significant role in different physiological as well as pathophysiological processes, such as transcription (Ji et al, 2022), translation (Chung et al, 2019), and mRNA stability (Cao et al, 2022). Above all, HNRNPR was proved to be multifunctional in diverse regulatory mechanisms, and no systematic study of HNRNPR in pan-cancer has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in tumors, growing evidence has demonstrated that HNRNPR plays a significant role in different physiological as well as pathophysiological processes, such as transcription (Ji et al, 2022), translation (Chung et al, 2019), and mRNA stability (Cao et al, 2022). Above all, HNRNPR was proved to be multifunctional in diverse regulatory mechanisms, and no systematic study of HNRNPR in pan-cancer has been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed that HNRNPR displays diverse cellular functions and widely participates in both physiological and pathophysiological processes. HNRNPR modulates transcription activation via the balance between 7SK/P‐TEFb and 7SK/hnRNP (Ji et al, 2022), promotes transcriptional activity of the c‐fos promoter (Fukuda et al, 2009), regulates the local messenger RNA (mRNA) availability and translation activity in axons (Chung et al, 2019), enhances LDLR stability through its 5'‐UTR RNA regions to affect lipid metabolism (Cao et al, 2022), participates in neuronal cholesterol metabolism by exerting repressive activity on HMGCR (Agbo et al, 2021). Missense or truncating of HNRNPR is associated with developmental defects, such as brain abnormalities (Duijkers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, at least 9 of the 15 genes with conserved splicing changes encoded for proteins that can affect gene expression (bolded genes in the inset of Fig. 6E ), including those encoding H3K27 demethylase KDM6A and transcriptional coactivator GPBP1 (Hsu et al, 2003 ) in eight datasets, as well as H3K36 methyltransferase NSD2 , splicing factor and transcriptional regulator HNRNPR (Ji et al, 2022 ), histone and non-histone protein deacetylase SIRT1 (Wang et al, 2019 ; Gan et al, 2020 ), the NuA4/TIP60 complex subunit EPC1 , and the H3K14ac histone reader BAZ2B that is part of chromatin remodeling complexes (Oppikofer et al, 2017 ) (Figs. 6E,G and EV4B; Dataset EV5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The primary function of BRD4 involves organizing super‐enhancers (SEs) and regulating oncogene expression (Di Micco et al, 2014; Donati et al, 2018). Specifically, as an epigenetic reader, BRD4 recognizes acetylated lysine residues on histones H3 and H4 (Shi & Vakoc, 2014) and mediates transcription initiation and elongation after recruiting the Mediator complex, positive transcription elongation factor b (P‐TEFb) and RNA polymerase II (Ji et al, 2022; Khoueiry et al, 2019). According to recent studies, BRD4 may contribute to the progression of breast cancer, gastric cancer, ovarian cancer, and head and neck squamous cell carcinoma (Drumond‐Bock & Bieniasz, 2021; Nagarajan et al, 2020; Qin et al, 2019; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%